Rudat Sasambo (RUSA) Diabetes Mellitus Exercise According to FITT, Reduce Blood Glucose Levels in Patients with Type 2 Diabetes Mellitus - Awan Dramawan; Intan Gumilang Pratiwi (Alliance oh Health Activists (AloHA), 2024)
Based on observations of the implementation of Diabetes Mellitus exercise carried out in several Mataram City communities, the problems that arise are the low participation of diabetics in the gymnastics program, the exercises carried out are not in accordance with good FITT such as frequency, intensity, tempo and type, in the observations of researchers at Persadia Mataram members. and members of the prolanis at the Community Health Center whose frequency is only once a week and some are once a month, not given a good intensity of training because the maximum pulse rate is not measured, the time given is 1 hour and the type of exercise is diabetes mellitus exercise which it is quite tiring, and counseling about the benefits of diabetes exercise has never been done, especially biometric parameters that will change if physical exercise such as blood glucose and uric acid is carried out, in the preliminary research conducted there was a decrease in blood glucose levels and blood pressure. uric acid in people with diabetes mellitus but there is an increase again because it is only done once a week or a month. This study aims to prove that Rudat Sasambo (RUSA) diabetes mellitus exercise according to FITT lowers blood glucose levels and uric acid levels compared to conventional diabetes mellitus exercise. The research design used in this study was a quasi-experimental, with a randomized control group pretest - posttest design. The sampling used was probability sampling with a simple random sampling approach. In this study, six measurements were taken where measurements were made before treatment and measurements after treatment which were then analyzed using an independent t-test and paired t-test. The results showed that there was an effect of RUSA diabetes mellitus exercise according to FITT on reducing blood glucose and uric acid, but there was no significant difference between diabetes mellitus exercise according to FITT and conventional diabetes mellitus exercise. Keywords: diabetes militus; exercise; blood glucose level; urid acid level